UNSTEADY MAGNETOHYDRODYNAMICS (MHD) FLOW OF FOURTH GRADE FLUID BETWEEN HORIZONTAL STATIONARY PLATES WITH VISCOUS DISSIPATION AND SUCTION EFFECTS - T. Zakari, Nasiru; E. Andi, Ayankop; K. Moses, Joseph; A.A, Wachin; B. Hassan, Joshua (FUDMA Journal of Sciences, 2025)
The unsteady magnetohydrodynamics (MHD) flow of fourth grade fluid between horizontal stationary plates with viscous dissipation and suction effects has been investigated. The fluid is subjected to a uniform transverse magnetic field. The upper and lower plates are stationary. The partial differential equations that govern the flow are the momentum and energy equations. For the solution of the fluid flow model, the He- Laplace method was employed. The effect of various flow parameters on velocity and temperature profile were obtained. Investigated were the effects of suction parameter, third and fourth grade parameters and Hartman number on velocity profile. Graph were plotted for each case considered. Results of this research show that temperature field increases with increase in Eckert number and radiation parameter but decrease with increases in suction parameter and Prandtl number. While for velocity field, it is observed that it decreases with increase in suction parameter and Hartman number, but increases with increase in third and fourth grade parameters. The result of this research would be useful in Engineering fields such as Bioengineering enhance oil recovery and medical science of complex fluid in development of magnetic device for cell separation and targeted transport of drugs carriers, etc.